The perceptions of healthcare administrativors on the adoption of home grown medical technology in Malaysian hospitals / Mailud Abdullah Hamed Balal - Hamed Balal, Mailud Abdullah (Institute of Graduate Studies, UiTM, 2018)
This research attempts to create a model that establishes the crucial aspects that affect the adoption decision of home grown medical technology (HGRMT) in developing countries. In this study, the proposed integrated model includes four key groups of factors: organizational factors, technological innovation factors, environmental factors based on TOE model Tornatzky et al (1990) enhanced with IDT theory Roger (1983), and individual factors based on intention based theories, particularly, TAM by Davis et al. (1989). This model proposes that there is a direct relationship between the mentioned factors and the adoption of HGMT in healthcare firms. A quantitative research methodology was applied in this research, with SEM as a tool of data analysis. Some of 40 Malaysian hospitals where randomly selected to collect the data using questionnaire. The empirical findings obtained from this study revealed that five out of eight suggested variables in the model namely, organizational readiness, compatibility, social networks, government support, manager's attitude were significant contributors to the adoption of HGRMT…